Karton Gelombang Dinding Tunggal Sebagai Bahan Kemasan Bunga Potong Segar Untuk Ekspor - Zoherly Zoherly (Balai Besar Kimia dan Kemasan, 1997)
Experiment using corrugated box made from single wall corrugated board to replace the existing double wall corrugated board has been conducted by comparing their physical properties.The result shows that the 30011501300 and 30011251300 structure of single wall corrugated boards have better physical properties compare to the existing double wall corrugated board which means that packaging of fresh cut flower for export can be made from the single wall corrugated board. Besides, the standardization of the corrugated box format based on the pallet efficiency, is described.